2008
DOI: 10.1038/msb.2008.57
|View full text |Cite
|
Sign up to set email alerts
|

An integrated cell‐free metabolic platform for protein production and synthetic biology

Abstract: Cell-free systems offer a unique platform for expanding the capabilities of natural biological systems for useful purposes, i.e. synthetic biology. They reduce complexity, remove structural barriers, and do not require the maintenance of cell viability. Cell-free systems, however, have been limited by their inability to co-activate multiple biochemical networks in a single integrated platform. Here, we report the assessment of biochemical reactions in an Escherichia coli cell-free platform designed to activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
399
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(412 citation statements)
references
References 44 publications
12
399
0
1
Order By: Relevance
“…Previously, we showed that approximately 100% of the CAT produced during the initial protein synthesis period (the first hour) is active (21,22). Thus, in the experiments performed here, the TCA-precipitable counts were a good indication of the active protein concentration.…”
Section: Gtpsupporting
confidence: 65%
See 1 more Smart Citation
“…Previously, we showed that approximately 100% of the CAT produced during the initial protein synthesis period (the first hour) is active (21,22). Thus, in the experiments performed here, the TCA-precipitable counts were a good indication of the active protein concentration.…”
Section: Gtpsupporting
confidence: 65%
“…The fraction of incorporated leucine was obtained by dividing the cpm of the precipitated sample by the cpm of the nonprecipitated sample. To illustrate, the following is a sample calculation if the TCA-precipitated count was 950 cpm, the nonprecipitated count was 9,996 cpm, and the background count from an experiment without plasmid DNA was 73 cpm (Table 1): {[(950 cpm Ϫ 73 cpm)/9,996 cpm] ϫ 2,000 M ϫ 25,000 g/mol}/(13 ϫ 1,000 ml/liter) ϭ 337 g CAT/ml.Previously, we showed that approximately 100% of the CAT produced during the initial protein synthesis period (the first hour) is active (21,22). Thus, in the experiments performed here, the TCA-precipitable counts were a good indication of the active protein concentration.…”
supporting
confidence: 65%
“…Here, we extend a scalable in vitro biochemical protein synthesis system, termed open cell-free synthesis (OCFS), 18,19 to the production of correctly folded antibody fragments and an aglycosylated version of anti-HER2 IgG1 trastuzumab. In vitro protein synthesis systems whereby a cell extract from E. coli cells harvested in exponential phase serves as a source of ribosomes and other cellular factors for translation 20 offer an alternative expression system that avoids many of the problems of conventional cell-based expression technologies.…”
Section: Resultsmentioning
confidence: 99%
“…Improvements in protein expression and access to stable enzymes have made more complex systems possible, however 1,[9][10][11][12] . In vitro biotransformation systems have been reported in recent years involving systems of over 30 enzymes 13,14 .…”
mentioning
confidence: 99%